Continuous subcutaneous insulin infusion in diabetes mellitus. A year's prospective trial. Issue 11 (November 1984) - Davies, A G; Price, D A; Houlton, C A; Burn, J L; Fielding, B A; Postlethwaite, R J
Abstract : Thirteen children aged between 8 and 16 years were entered into a 12 month prospective trial comparing continuous subcutaneous insulin infusion with intensified conventional treatment. Two of seven children on insulin infusion withdrew after eight and nine weeks, and three of six children on conventional treatment withdrew after four to eight weeks. Withdrawals in both groups were related to dissatisfaction with the techniques. The group on insulin infusion treatment achieved a mean plasma glucose of 9.8 mmol/l (176.4 mg/100 ml), a median M value of 50 mmol/l (900 mg/100 ml) and a mean glycosylated haemoglobin of 9.1% during the year. This represents a significant improvement compared with the previous values, and also when compared with the conventional treatment group whose trial values of a mean plasma glucose of 15.5 mmol/l (279 mg/100 ml), median M value of 167 mmol/l (3006 mg/100 ml), and glycosylated haemoglobin of 10.4% were not significantly different from those before the trial. Two children on insulin infusion developed subcutaneous abscesses in the early months. There was an increased incidence of diabetic ketoacidosis in this group, but no difference in the incidence of serious hypoglycaemia between the two groups. The children reported improved well-being when using insulin infusion and continued with the technique after the trial finished. Insulin infusion offers an acceptable means of improving glycaemic control for some diabetic children.